Role of species-specific primary structure differences in Aβ42 assembly and neurotoxicity - Roychaudhuri, Robin (ACS Chem Neurosci, 2015)
A variety of species express the amyloid β-protein (Aβ). Those species expressing Aβ with primary structure identical to that expressed in humans have been found to develop amyloid deposits and Alzheimer’s disease-like neuropathology. In contrast, the Aβ sequence in mice and rats contains three amino acid substitutions, Arg5Gly, His13Arg, and Tyr10Phe, which apparently prevent the development of AD-like neuropathology. Interestingly, the brush-tailed rat, Octodon degus, expresses Aβ containing only one of these substitutions, His13Arg, and does develop AD-like pathology. We investigate here the biophysical and biological properties of Aβ peptides from humans, mice (Mus musculus), and rats (Octodon degus). We find that each peptide displays statistical coil→β-sheet secondary structure transitions; transitory formation of hydrophobic surfaces; oligomerization; formation of annuli, protofibrils, and fibrils; and an inverse correlation between rate of aggregation and aggregate size (faster aggregation produced smaller aggregates). The rank order of assembly rate was mouse > rat > Aβ42. The rank order of neurotoxicity of assemblies formed by each peptide immediately after preparation was Aβ42 > mouse ≈ rat. These data do not support long-standing hypotheses that the primary factor controlling development of AD-like neuropathology in rodents is Aβ sequence. Instead, the data support a hypothesis that assembly quaternary structure and organismal responses to toxic peptide assemblies mediate neuropathogenetic effects. The implication of this hypothesis is that a valid understanding of disease causation within a given system (organism, tissue, etc.) requires the co-evaluation of both biophysical and cell biological properties of that system.